The spread of Keynesianism in Brazil: The origins and experience of the Brazilian Keynesian Association - Luiz Fernando de Paula; Fernando Ferrari Filho (Intervention. European Journal of Economics and Economic Policies, 2010)
First paragraph: In a paper presented at the 8th Annual Conference of the Brazilian Society for Political Economy, in June 2003, Victoria Chick (2004: 3) wrote: »There are many pleasures attached to being in Brazil, but one of the chief intellectual pleasures is that Brazil is still a centre of heterodox economic thought. Perhaps this is for an unfortunate reason, namely that Brazil is beset with economic problems, and serious problems require practical solutions«. Pointing in the same direction, in a paper prepared for the 1st Meeting of the Brazilian Keynesian Association (Associaç\~ao Keynesiana Brasileira – AKB), Fernando Cardim de Carvalho (2008: 569, translated by the authors) wrote: »For many years it has been noted, with some surprise, that the thinking of Keynes and his followers exerts a strong influence on Brazilian economic thought. Even in the gloomy 1980s when, especially in North American academic circles, the so-called New Classics school emerged with a force as intense as it was ephemeral, the community of academic economists in Brazil continued to cultivate the legacy of great economists such as, but not only, Keynes, Kalecki and Schumpeter, to name just a few.« The relationship between the application of heterodox counter-cyclical economic policies, identified with Brazilian economic thinking, and the Brazilian economy's performance is a matter of fact: In the period when Brazil's economy enjoyed vigorous growth (averaging around 7.0 % per year), i.e., from after World War II to the end of the 1970s, there was active state intervention into the economy and heterodox economic policies predominated. As a result, in that same period, Brazil's economy underwent important structural changes, although maintaining high levels of social inequality. Since the early 1980s, meanwhile, the Brazilian economy has been conspicuous for its stop-and-go performance and relatively slow growth (averaging 2.5 % per year from 1980 – 2008). That period is identified, on the one hand, with strongly accelerating inflation in the 1980s and failed heterodox stabilisation plans and, on the other hand, by the introduction, in both Brazil and Latin America more widely, of neoliberal policies in the 1990s. This included trade liberalisation, market deregulation, privatisation of state enterprises, financial liberalisation (capital account deregulation and more flexible rules on foreign bank operations in Brazil) and so on – in the context of the economic policy recommendations of what came to be known as the Washington Consensus (Williamson 1990). However, the vulnerability of the Brazilian economy (and other Latin American economies) to contagion by external crises, with adverse effects on production and employment, meant that by the late 1990s and the 2000s the policies advocated by the Washington Consensus were called into question.
Keywords: 330